2016
DOI: 10.1016/j.biopsycho.2016.04.066
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of cortisol response to social evaluative threat with autonomic and inflammatory responses is moderated by stress appraisals and affect

Abstract: Recent approaches to stress regulation have emphasized coordination among multiple biological systems. This study builds on evidence that hypothalamic-pituitary-adrenal (HPA) axis activity should be considered in coordination with other stress-sensitive biological systems to characterize healthy responses. Healthy African-Americans (n=115) completed the Trier Social Stress Test, and biological responses were assessed through salivary cortisol, dehydroepiandrosterone-sulfate (DHEA-S), alpha amylase (sAA), and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(76 citation statements)
references
References 42 publications
4
71
1
Order By: Relevance
“…A wealth of evidence suggests that inflammation and dysregulation of HPA axis are independently associated with MDD (Pariante & Lightman, 2008) including onset of MDD among at-risk individuals (Mannie, Harmer, & Cowen, 2007; Owens, et al, 2014). Only recently have studies begun to employ a multisystem approach to explore the complex biological underpinnings of MDD and vulnerability with preliminary results underscoring differences in patterns of neuro-immune perturbations associated with depressive subtypes (e.g., Lamers, et al, 2013; Laurent, et al, 2016) and gender-specific vulnerability. To date, however, no study had employed a multisystem approach when examining NA reactivity to stress as a function of depressive symptom severity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A wealth of evidence suggests that inflammation and dysregulation of HPA axis are independently associated with MDD (Pariante & Lightman, 2008) including onset of MDD among at-risk individuals (Mannie, Harmer, & Cowen, 2007; Owens, et al, 2014). Only recently have studies begun to employ a multisystem approach to explore the complex biological underpinnings of MDD and vulnerability with preliminary results underscoring differences in patterns of neuro-immune perturbations associated with depressive subtypes (e.g., Lamers, et al, 2013; Laurent, et al, 2016) and gender-specific vulnerability. To date, however, no study had employed a multisystem approach when examining NA reactivity to stress as a function of depressive symptom severity.…”
Section: Resultsmentioning
confidence: 99%
“…Emerging evidence has suggested that depressive subtypes and vulnerabilities to depression are associated with distinct patterns of dysregulation between the HPA axis and immune response system (IRS) (Lamers, et al, 2013; Suarez, et al, 2014) and between the HPA axis and autonomic nervous system (ANS) (Laurent, Lucas, Pierce, Goetz, & Granger, 2016). Although different markers of system activities have been employed to evaluate individual system activities, the general conclusion derived by these study is that a disorganization between inter-related systems provides a more complete picture of underlying pathophysiology associated with MDD and vulnerability than dysregulation of any single system (Schumacher, Kirschbaum, Fydrich, & Strohle, 2013).…”
mentioning
confidence: 99%
“…CRP can be detected in saliva (sCRP) and research has shown that CRP can pass from blood to saliva through gingival crevicular fluid, indicating that sCRP can be indicative of both local and systemic inflammation (Megson, Fitzsimmons, Dharmapatni, & Mark Bartold, ). Furthermore, several studies have found that sCRP is associated with measures of both psychological and physical health in children and adults (Cicchetti, Handley, & Rogosch, ; Goodson et al ., ; Laurent, Lucas, Pierce, Goetz, & Granger, ; Lucas et al ., ; Naidoo, Konkol, Biccard, McKune, & Dubose, ) as well as neural responses to emotional processing of stress (O'Connor, Irwin, & Wellisch, ), suggesting that it is also a useful measure of not only oral inflammation, but also more systemic health status.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, only when complementary measurements of the endocrine milieu were incorporated into the analytical plan did relationships with depression emerge. These findings underscore the value of examining cortisol levels together with other hormonal responses (Bauer et al, 2002; Laurent et al, 2016; Mehta and Josephs, 2010; Mendes et al, 2007) that may modulate the effects of cortisol on emotional and behavioral health outcomes.…”
Section: Discussionmentioning
confidence: 83%
“…The assay used 100 μL of saliva per determination, had a lower limit of sensitivity of <43 pg/mL, standard curve range from 188.9 pg/mL to 15,300 pg/mL, an average intra-assay coefficient of variation of 7.3% and an inter-assay coefficient of variation of 7.6%. Following prior work (Laurent et al, 2016), we assessed the sulfated form (DHEA-S), which is more biologically active than DHEA.…”
Section: Methodsmentioning
confidence: 99%